Предмет: Алгебра,
автор: sweetprojekt1
Решите уравнение : (2x-4)*(6x+3)=(3x-2)*(4x-1)
СРОЧНО
Ответы
Автор ответа:
0
(2x-4)*(6x+3)=(3x-2)*(4x-1)
12х²+6х-24х-12=12х²-3х-8х+2
12х²+6х-24х-12х²+3х+8х=2+12
-7х=14
х=14:(-7)
х=-2
Ответ:-2
12х²+6х-24х-12=12х²-3х-8х+2
12х²+6х-24х-12х²+3х+8х=2+12
-7х=14
х=14:(-7)
х=-2
Ответ:-2
Автор ответа:
0
ОК!
Похожие вопросы
Предмет: Математика,
автор: amvanchan
Предмет: История,
автор: ipsarspaprpr
Предмет: Геометрия,
автор: tolubicki46
Предмет: Литература,
автор: мур5
Предмет: Физика,
автор: yuipru